Associations of Subjective Social Status with Physical Activity and Body Mass Index across Four Asian Countries. (28th May 2014) - Frerichs, Leah; Huang, Terry T.-K.; Chen, Duan-Rung
Abstract : Objective . The aims of this study were to (1) assess physical activity and weight status differences and (2) explore the direction and shape of subjective social status (SSS) association with physical activity and weight status within four Asian countries. Methods . Cross section data of adult respondents from the nationally representative East Asian Social Survey were used for analyses. Logistic regression stratified by gender was conducted for the first aim, and simple and quadratic logistic regression models were used for the second. Results . SSS was significantly associated with odds of weekly or daily physical activity across all countries and genders, except for South Korean and Japanese females. Quadratic models provided significantly better fit for Chinese males (LR (d.f. = 1) = 6.51, P value< .05 ) and females (LR (d.f. = 1) = 7.36, P value< .01 ), South Korean males (LR (d.f. = 1) = 4.40, P value< .05 ), and Taiwanese females (LR (d.f. = 1) = 4.87, P value< .05 ). Conclusions . This study provides a comparable cross Asian country measure of moderate-to-vigorous physical activity and new findings that a connection exists between SSS and physical activity. Differences of class distinction help explain the different shaped SSS relationships.